2021
DOI: 10.1111/gcbb.12790
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and methane yield of giant reed (Arundo donaxL.) as affected by single and double annual harvest

Abstract: The replacement of silage maize with giant reed as energy crop has been proposed as a mean for reducing the need of irrigation water as well as monetary and environmental costs of cultivation. Little is known about giant reed response to within‐season harvesting, and its effect on the methane production in anaerobic digestion. The effect of three harvest schedules on yield, biomass composition and methane production of giant reed was evaluated at one site of the Po Valley, northern Italy, for three consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…These SMY values are in line with the CH 4 yield obtained from other substrates commonly used in AD such as, for example, cattle slurry, wheat straw, vegetable waste, garden waste [3,36] or from Brassica napus which recently was reported to yield up to 259 mL CH 4 g −1 VS when irrigated with abattoir wastewater [37]. In this study, untreated giant reed (GR) reached 192 mL CH 4 g −1 VS, which is consistent with what was reported by other authors for this crop [17,38] and is comparable with the SMY of miscanthus, which varied between 166 and 202 mL CH 4 g −1 VS, depending on the genotype [18].…”
Section: Effects Of the Pre-treatments On Anaerobic Digestionsupporting
confidence: 91%
“…These SMY values are in line with the CH 4 yield obtained from other substrates commonly used in AD such as, for example, cattle slurry, wheat straw, vegetable waste, garden waste [3,36] or from Brassica napus which recently was reported to yield up to 259 mL CH 4 g −1 VS when irrigated with abattoir wastewater [37]. In this study, untreated giant reed (GR) reached 192 mL CH 4 g −1 VS, which is consistent with what was reported by other authors for this crop [17,38] and is comparable with the SMY of miscanthus, which varied between 166 and 202 mL CH 4 g −1 VS, depending on the genotype [18].…”
Section: Effects Of the Pre-treatments On Anaerobic Digestionsupporting
confidence: 91%
“…Giant reed biomass has found wide applications in energy production; it can be used in combustion, gasification and pyrolysis and to produce biogas [1]. In fact, when harvested in autumn its biomass can be used in anaerobic digestion in substitution/partial integration with the traditional energy crops [48][49][50], and the biomass harvested in winter can be used for the combustion process, due to its high heating value of about 18.7 MJ kg −1 [1].…”
Section: Discussionmentioning
confidence: 99%
“…The Bologna province (BO, Emilia Romagna region) contains an overall ML area of 880 km 2 . The climate in the region is temperate sub-continental, characterized by relatively high temperatures and evenly distributed precipitation throughout the year [25]. Average annual air temperature is about 13 • C, fluctuating from 0 to 5 • C in winter months, to peaks over 30 • C in the period June-August.…”
Section: Study Area and Bionergy Sector Maturitymentioning
confidence: 99%
“…Furthermore, the very deep root system allows the crop to adsorb soil pollutants, favoring soil phytoremediation and aggregation [10]. Thanks to the advantageous balance between biomass yield, fiber composition and amount and cost of agronomic inputs needed to grow the crop under unstressed conditions, giant reed, as a second-generation energy source, demonstrated to provide higher energy yield per hectare compared to conventional crops also in Mediterranean and Italian environments [17,24,25]. Corno et al [24] reported that giant reed produces on average 11,000 L ha −1 of bioethanol, which is approximately 1.25 times more than the yield obtainable from miscanthus, 1.8 times more than sugar cane and sugar beet, and 3.7 times more than corn and sweet sorghum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation